The ANALYSIS OF INCREASED SOCIAL INTERACTION THROUGH TRADITIONAL SPORTS GAMES IN ELEMENTARY SCHOOL STUDENTS - Mulyani, Tresna; Kurniawati, Ani; Sonjaya, Azhar Ramadhana; Kosasih, Alam Hadi (JUARA : Jurnal Olahraga, 2024)
Physical education is one of the subjects in schools, including elementary schools. Learning to swim is not easy as experienced by 6th grade students of SDN 2 Pataruman Garut. Where they still have a lot of difficulty in doing social interactions. One of the learning methods that can be used in this case is the Direct Instruction (DI) method with a Video Media approach and game application. This study aims to determine the effect in improving the results of social interaction through traditional sports on 6th grade students of SDN 2 Pataruman Garut. Direct learning method assisted by video media, is very good for improving the results of students' social interaction quite significantly. From the results of the analysis obtained a significant increase from cycle 1, cycle 2 and cycle 3. The results of social interaction through traditional sports in cycle 1 in the Good category were 8% the number of students who completed was 15 students. In cycle 2 there was an increase in the percentage of students' social interactions in the Good category by 40%, while 23 students were complete. In cycle 3, there was an increase in students' social interactions in the good category by 64% while 24 out of 25 students were complete